The narration of the Video Game in the labyrinth of the Mise en Abyme" (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Video games incorporate into traditional storytelling the ability to tell stories through actions carried out by player characters. This is only possible because video game narration has taken new expressive paths along which to make its stories travel: as opposed to the linearity of paths traced in a single direction, typical of classic exercises, the labyrinth of paths in multiple directions specific to the video game, and whose interpretation is finally carried out by the player-character, only after an intricate exercise of "mise en abyme".
Keywords: videogame; hypertex; mise en abyme; characters; narrative labyrinth